Designable ultra-smooth ultra-thin solid-electrolyte interphases of three alkali metal anodes - Gu, Yu; Wang, Wei-Wei; Li, Yi-Juan; Wu, Qi-Hui; Tang, Shuai; Yan, Jia-Wei; Zheng, Ming-Sen; Wu, De-Yin; Fan, Chun-Hai; Hu, Wei-Qiang; Chen, Zhao-Bin; Fang, Yuan; et al. (Nature communications, 2018)
Dendrite growth of alkali metal anodes limited their lifetime for charge/discharge cycling. Here, we report near-perfect anodes of lithium, sodium, and potassium metals achieved by electrochemical polishing, which removes microscopic defects and creates ultra-smooth ultra-thin solid-electrolyte interphase layers at metal surfaces for providing a homogeneous environment. Precise characterizations by AFM force probing with corroborative in-depth XPS profile analysis reveal that the ultra-smooth ultra-thin solid-electrolyte interphase can be designed to have alternating inorganic-rich and organic-rich/mixed multi-layered structure, which offers mechanical property of coupled rigidity and elasticity. The polished metal anodes exhibit significantly enhanced cycling stability, specifically the lithium anodes can cycle for over 200 times at a real current density of 2 mA cm –2 with 100% depth of discharge. Our work illustrates that an ultra-smooth ultra-thin solid-electrolyte interphase may be robust enough to suppress dendrite growth and thus serve as an initial layer for further improved protection of alkali metal anodes. The dendrite growth of alkali metal anodes leads to charge/discharge cycling instability. Here, the authors show that electrochemical polishing can yield near-perfect anodes of three alkali metals by constructing smooth and thin solid-electrolyte interphase layers.